2022
DOI: 10.3390/app12073650
|View full text |Cite
|
Sign up to set email alerts
|

A Place to Be? Use of Winter Gardens with and without Automatic Enrichment Devices by Laying Hens

Abstract: Since the abolition of beak trimming in laying hens in Germany, the importance of adequate enrichment material to help reduce feather pecking and cannibalism has grown. Here we tested an automatic enrichment device dosing grain via rough-coated pecking plates (PPs) on an organic farm, comparing its offer in four winter gardens (WGs). Winter garden (WG) 1 served as the control area without an automatic enrichment device, while WGs 2–4 offered different quantities of PPs, with WG 2 offering double the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, the majority of the time spent outside the house was spent in the veranda (58% reported by (Larsen et al, 2017); and 71% reported by (Gebhardt-Henrich et al, 2014)). Riedel et al (2022) reported that 8% of the flock was present in the veranda on average, which was increased to 12% if grain dosing devices were provided. Some newly developed systems have extended covered verandas but allow no or very limited outdoor access.…”
Section: Covered Verandamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the majority of the time spent outside the house was spent in the veranda (58% reported by (Larsen et al, 2017); and 71% reported by (Gebhardt-Henrich et al, 2014)). Riedel et al (2022) reported that 8% of the flock was present in the veranda on average, which was increased to 12% if grain dosing devices were provided. Some newly developed systems have extended covered verandas but allow no or very limited outdoor access.…”
Section: Covered Verandamentioning
confidence: 99%
“…Riedel et al. (2022) reported that 8% of the flock was present in the veranda on average, which was increased to 12% if grain dosing devices were provided. Some newly developed systems have extended covered verandas but allow no or very limited outdoor access.…”
Section: Assessmentmentioning
confidence: 99%
“…Therefore, on two days of each phase in the time between 14:00 and 16:00, 10 randomly selected hens were observed. This time was chosen on the basis of hen counts from the same WGs [ 25 ], indicating times when the area was well frequented and no feeding times in the henhouse were programmed. The program GoldenRatio (Version 3.1, Markus Welz, Krailling, Germany) was used to outline the observed area consistently in every video.…”
Section: Methodsmentioning
confidence: 99%
“… ( a ) Scheme of the henhouse and winter gardens (WGs 1–4) with the downpipes with pecking plates indicated with red dots; ( b ) photograph of the enrichment device with the pecking plate circled in red (photo: A. Riedel). Adapted from [ 25 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation